A Meta-Analysis of Autologous Microsurgical Breast Reconstruction and Timing of Adjuvant Radiation Therapy - Heiman, Adee J.; Gabbireddy, Sairisheel R.; Kotamarti, Vasanth S.; Ricci, Joseph A. (Journal of Reconstructive Microsurgery, 2020)
Background Postmastectomy radiation therapy (PMRT) decreases loco-regional recurrence and improves survival in patients with locally advanced breast cancer. Autologous free flap reconstruction, while more durable in the setting of radiation than alloplastic reconstruction, is still susceptible to radiation-induced fibrosis, contracture, fat necrosis, volume loss, and distortion of breast shape. Options for reconstruction timing (immediate vs. delayed) have been discussed to mitigate these effects, but a clear optimum is not known.Methods A systematic review of the literature was conducted according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines using search terms “breast reconstruction AND (radiation OR irradiation OR radiotherapy)” were used. Inclusion criteria consisted of studies reporting complications for free flap breast reconstruction in the setting of PMRT. Patients who underwent PMRT were pooled into two groups: those who underwent immediate free flap reconstruction prior to PMRT and those who underwent delayed reconstruction after PMRT.Results Out of the 23 studies, 12 focused on immediate reconstruction, seven focused on delayed reconstruction, and four studies included both groups. Overall, 729 patients underwent immediate reconstruction, while 868 underwent delayed reconstruction. Complete and partial flap loss rates were significantly higher in patients undergoing delayed reconstruction, while infection and wound-healing complication rates were higher in those undergoing immediate reconstructions. Rates of unplanned reoperations, vascular complications, hematoma/seroma, and fat necrosis did not differ significantly between the two groups. However, rates of planned revision surgeries were higher in the delayed reconstruction group.Conclusion Immediate free flap breast reconstruction is associated with superior flap survival compared with delayed reconstruction. Rates of complications are largely comparable, and rates of revision surgeries are equivalent. The differences in long-term aesthetic outcomes are not, however, clearly assessed by the available literature. Even in the face of PMRT, immediate free flap breast reconstruction is an effective approach.
Keywords: autologous breast reconstruction; immediate breast reconstruction; delayed breast reconstruction; microsurgery; postmastectomy radiation therapy